Regional Government Authority in Fulfilling the Right to Legal Aid for the Poor and Vulnerable Groups - Indah Sari; Aminuddin Ilmar (Universitas Islam Negeri Alauddin Makassar, 2022)
Local government is authorised to fulfil the right to legal aid to disadvantaged and vulnerable groups. Such authority is referred to as attributive authority. The regional government's implementation of legal aid is critical because the central government's budget allocation for such aid remains constrained. This is evident from the unequal distribution of funds for legal aid as well as the disparity between the number of legal aid organisations and the number of people in need. In addition to being constrained by the budget, the provision of legal aid under Law No. 16 of 2011 concerning Legal Aid is currently confined to the poor, despite the fact that various laws mandate the provision of legal aid to certain groups.